Geographic Information Systems for Appraisal of Spatial Disparities of Air Pollution in Karachi - Mudassar Hassan Arsalan (JISR Management and Social Sciences & Economics, 2004)
Air pollution is a major environmental health problem affecting the developed as well as developing countries around the world. Continuous growth of human induced unchecked sources of pollution is the pivotal point of this burgeoning problem.GIS has largely been employed for environmental inquiries in the developed world. In Pakistan, these technologies are in their introductory phases. However, it is a pioneering attempt of using Geographic Information Systems to evaluate the spatial variations of air pollution. The study area is Karachi metropolis, the largest city in Pakistan. Traffic and industrial activity have been identified as the major sources of pollution in Karachi. The ultimate Risk Zone map is clearly demonstrating the spatial patterns of air pollution in Karachi. The built-up localities of old city area, Landhi Korangi industrial/residential area, and SITE Industrial region are under high risks on an aggregate level.